THE CONTINUAL IMPROVEMENT IN THE CERTIFICATION OF COFFEE FARMS: A CASE STUDY - Castro, Claúdio Vieira; Lira, Jean Marcel Sousa; Salgado, Eduardo Gomes; Beijo, Luiz Alberto (Coffee Science - ISSN 1984-3909, 2018)
The certification of agricultural products is considered a strategy that promotes sustainability and appreciation of product. In coffee production, the Certifica Minas Café is the only public coffee certification program in Brazil. However, over the years, many coffee farms that have this certification reduce their competence to meet the requirements, stabilizing at minimum levels of compliance, which allows maintaining the certificates, but does not promote continual improvement. Therefore, this study aimed to evaluate the effect of Certifica Minas Café certification on the improvement of sustainability over time on coffee farms. For this, a case study with two properties in the south of the state of Minas Gerais was carried out, in which one of them quest to achieve continuous improvement, while the other did not. On the coffee farm of the first case was observed a reduction in investment and low concern to maintain the requirements established by the certification, while the coffee farm of the second case reduced the number of requirements requested by the certification program over time. Lastly, this paper hypothesizes that improvement of sustainability depends on understanding the benefits of certification in the long term and is related to a behaviour change by the certified farm.